The consequences of social intolerance on non-violent protest - Rapp, Carolin; Ackermann, Kathrin (European political science review, 2016)
This paper scrutinizes the impact of intolerance toward diverse ethnic, religious, and cultural groups on an individual’s willingness to actively engage in non-violent protest. Following new insights, we examine the individual as well as the ecological effect of social intolerance on protest behavior. Drawing from insights of social psychology and communication science, we expect that the prevalence of intolerance reinforces the positive effect of individual-level intolerance on protest participation. From a rational choice perspective, however, a negative moderating effect is expected, as the expression of opinions becomes redundant for intolerant individuals in an intolerant society. We base our multilevel analyses on data from the World Values Surveys covering 32 established democracies. Our results reveal that intolerance leads to more non-violent protest participation. This relationship, however, is strongly influenced by the prevalence of intolerance in a country.
Published online by Cambridge University Press: 03 July 2015
Gesehen am 14.04.2021